The Effect of Student Motivation, Example, Personality, and Learning Strategies on the Growth of Character Value in State SMA Students in Salatiga City for the Academic Year 2021/2022 - Nurbaedi, Amin; Sugiyo, Sugiyo; Hasyim, A. Dardiri (Language Circle: Journal of Language and Literature, 2022)
The formation of a quality generation is started from an output of Islamic education that it has both as individuals, socially, and believes in God Almighty. Indicators that appear in the current dynamics are rampant brawls, immoral acts, and a lack of etiquette in the association among students. The restructuring or transformation of Indonesia's national education is able to take advantage of the opportunities that are open and shape the character that contains the value of human behavior. This study uses a quantitative method with a correlational design, this study aims to determine the relationship of a variable with other variables by using a multiple linear regression test. Regression analysis is used to examine the relationship between two or more variables, especially to explore the pattern of relationships whose models are not yet fully known. The results of this study are: Student motivation has an effect on the growth of character values in State Senior High School students in Salatiga City; The example of PAI teachers have an effect on the growth of character values in State Senior High School students in Salatiga City; The personality of the PAI teacher has an effect on the growth of character values in State Senior High School students in Salatiga City; PAI teacher learning strategies affect the growth of character values in state high school students in Salatiga City; There is an effect of effectiveness on the variables of student motivation, exemplary, and GPAI learning strategies on the growth of character values in students in SMA Negeri in Salatiga City. The variable that has no effect on the growth of character values in students at SMA Negeri in Salatiga City is the personality variable.